Direct growth of GaN film on ScAlMgO4 substrate by radio-frequency plasma-excited molecular beam epitaxy. (15th February 2023) - Araki, Tsutomu; Kayamoto, Seiya; Wada, Yuuichi; Kuroda, Yuuya; Nakayama, Daiki; Goto, Naoki; Deura, Momoko; Mouri, Shinichiro; Fujii, Takashi; Fukuda, Tsuguo; Shiraishi, Yuuji; Sugie, Ryuichi
Abstract: ScAlMgO4 (SAM) has attracted attention as a substrate for nitride semiconductor crystal growth owing to its small a -axis lattice mismatch with GaN and InGaN. In this study, we investigated GaN growth on a SAM substrate via radio-frequency plasma-excited molecular beam epitaxy. By optimizing the growth conditions, GaN with the following epitaxial orientation relations (0001)GaN //(0001)SAM and [11–20]GaN //[11–20]SAM was successfully grown directly on the SAM substrate. The atomically flat and abrupt interface of GaN directly grown on the SAM substrate was observed via high-resolution transmission electron microscopy, and uniform GaN growth on a two-inch SAM substrate was also demonstrated.